Acute respiratory viral infections: Consensus on rational therapy - Andrey A. Zaytsev; Nina A. Miroshnichenko; Andrey Yu. Ovchinnikov; Yulia O. Nikolaeva (Consilium Medicum)
There are diseases for which people turn to specific specialists, but there are also a number of ones that are treated by doctors of different specialties. Therapists, infectious disease specialists, otolaryngologists, and pulmonologists diagnose and treat acute respiratory viral infections. But the same specialists often have to deal with the outcomes of an acute process – postnasal drip and post-infectious cough, which decreases the quality of life and exhaust patients. However, in case when the correct diagnosis is made, there are treatment regimens that allow to achieve quick relieve subjective and objective symptoms, as well as clinical cure of the disease escaping the use of antibacterial therapy. The efficient therapy agreement of the otolaryngologist and pulmonologist is that for various causes of cough, herbal medicine is the best choice.